Wet-process feasible candlelight OLED. Issue 25 (9th June 2016) - Jou, Jwo-Huei; Su, Yu-Ting; Liu, Shih-Hao; He, Zhe-Kai; Sahoo, Snehasis; Yu, Hui-Huan; Chen, Sun-Zen; Wang, Ching-Wu; Lee, Jia-Ren
Abstract : Candlelight-based, blue-hazard free lighting sources are friendly to the human eye, physiology, museum artifacts, ecosystems, the environment, and the night sky. Abstract : Candlelight-based, blue-hazard free lighting sources are friendly to the human eye and physiology, museum artifacts, ecosystems, the environment, and the night sky. Wet processing enables organic devices to be fabricated cost-effectively with a large area-size via continuous roll-to-roll manufacturing. We demonstrate here a candlelight organic light-emitting diode (OLED) using a wet process to deposit at least the layers of emission, hole-injection, and hole-transportation. The resulting 1918 K candlelight OLED is about 50 and 15 times safer to the retina and in terms of melatonin generation protection, respectively, as compared with the 5000 K white LED, CFL and OLED. It can reach a maximum brightness of 38 000 cd m −2, equivalent to 42 000 candlelight in one square meter, and its efficacy is 300 times that of candle and 3 times that of an incandescent bulb. This study may serve as a starting point to begin a healthy-light based "Lighting Renaissance" with feasible commercialization.